Angiographic Patency of Coronary Artery Bypass Conduits: A Network Meta‐Analysis of Randomized Trials - Mario Gaudino; Irbaz Hameed; N. Bryce Robinson; Yongle Ruan; Mohamed Rahouma; Ajita Naik; Viola Weidenmann; Michelle Demetres; Derrick Y. Tam; David L. Hare; Leonard N. Girardi; Giuseppe Biondi‐Zoccai; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Several randomized trials have compared the patency of coronary artery bypass conduits. All of the published studies, however, have performed pairwise comparisons and a comprehensive evaluation of the patency rates of all conduits has yet to be published. We set out to investigate the angiographic patency rates of all conduits used in coronary bypass surgery by performing a network meta‐analysis of the current available randomized evidence. Methods and Results A systematic literature search was conducted for randomized controlled trials comparing the angiographic patency rate of the conventionally harvested saphenous vein, the no‐touch saphenous vein, the radial artery (RA), the right internal thoracic artery, or the gastroepiploic artery. The primary outcome was graft occlusion. A total of 4160 studies were retrieved of which 14 were included with 3651 grafts analyzed. The weighted mean angiographic follow‐up was 5.1 years. Compared with the conventionally harvested saphenous vein, both the RA (incidence rate ratio [IRR] 0.54; 95% CI, 0.35–0.82) and the no‐touch saphenous vein (IRR 0.55; 95% CI, 0.39–0.78) were associated with lower graft occlusion. The RA ranked as the best conduit (rank score for RA 0.87 versus 0.85 for no‐touch saphenous vein, 0.23 for right internal thoracic artery, 0.29 for gastroepiploic artery, and 0.25 for the conventionally harvested saphenous vein). Conclusions Compared with the conventionally harvested saphenous vein, only the RA and no‐touch saphenous vein grafts are associated with significantly lower graft occlusion rates. The RA ranks as the best conduit. Registration URL: https://www.crd.york.ac.uk/prospero; Unique identifier: CRD42020164492.